2018
DOI: 10.18203/2394-6040.ijcmph20182419
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of educational outcomes of small group discussion versus traditional lecture format among undergraduate medical students

Abstract: Background: In present scenario, medical students are over burdened with high academic load making learning more complicated than simple. In the recent past a lot of importance has been given for active learning by implementing various approaches like tutorials, seminars, small group discussionsetc. Small group discussion enhances student-faculty interaction, improves communication skills and provides a platform to exchange of ideas, which will result in deeper learning and better academic achievements by stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
1
7
0
2
Order By: Relevance
“…Some studies showed that involvement of students in a large room or a lecture hall through voluntary participation in additional active learning exercises with aid of software [13] and use of game-like format of the review session and its custom-designed software, that combines interactivity, team learning and peer-to-peer instruction [14], resulted in an improvement in understanding and application of physiological concepts and enriched students’ learning experiences. Many Studies showed that students prefer learning approaches in which the students have more active role than the TL like case based learning [15], team based learning [16], small group discussion [17] and flipped classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that involvement of students in a large room or a lecture hall through voluntary participation in additional active learning exercises with aid of software [13] and use of game-like format of the review session and its custom-designed software, that combines interactivity, team learning and peer-to-peer instruction [14], resulted in an improvement in understanding and application of physiological concepts and enriched students’ learning experiences. Many Studies showed that students prefer learning approaches in which the students have more active role than the TL like case based learning [15], team based learning [16], small group discussion [17] and flipped classroom.…”
Section: Introductionmentioning
confidence: 99%
“…29 Begitu pula dengan penelitian Joshi et al yang mendapati 15 hari setelah intervensi kapasitas retensi peserta pada diskusi kelompok lebih tinggi daripada ceramah. 30 Metode ceramah memberikan tingkat retensi pengetahuan terendah dari metode belajar lainnya dan berkontribusi paling rendah terhadap fungsi kognitif. 31 Namun, ceramah dapat memberi pengaruh baik terhadap retensi peserta, diantaranya jika dilakukan dengan cara sebagai berikut: memberdayakan peserta dan membuat mereka tetap fokus, melibatkan mereka, menggerakkan peserta dan membuat mereka bersedia mempelajari lebih lanjut tentang topik yang dibahas, memberikan wawasan baru dan merangsang pemikiran serta analisis, membuat orang berpikir dan memotivasi mereka untuk mengembangkan keterampilan baru.…”
Section: Pengetahuan Sikap Dan Keyakinanunclassified
“…In this form of teaching and learning the facilitator is acting as a moderator and supervisor. [16][17][18][19][20] the approach for solving these case scenarios are theoretical and are generated by the learner. The individual groups investigate the probable and possible outcomes or solutions of the problems which will be shared in the next or other group session.…”
Section: Introductionmentioning
confidence: 99%
“…[21,23] The current curriculum, which expects at least one third of alignment and integration; both horizontal and vertical widely promotes use of self-directed learning which will help the learner to understand the subject or topic in intricate manner, improving knowledge retention, enhancing their critical thinking skills which is the need of current age and time. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] the present research was undertaken to analyse the bene ts of active learning in teaching physiology.…”
Section: Introductionmentioning
confidence: 99%